Integrated Geophysical Study to Delineate Subsurface Structures in Seri Iskandar, Perak: The Kati Formation - Shek Houng, Douglas Law (Universiti Teknologi PETRONAS, 2016)
The region of Seri Iskandar is regarded to as the extension of the Kati Formation which originates from the northern parts of the state of Perak. Having alternating beds of sandstone, shale, clay as well as siltstones, it is believed to once be a deep marine environment. This study is done in accordance to image the subsurface structures of Seri Iskandar by integrating several geophysical methods. Due to heavy weathering by extreme climate, outcrops studies of the Kati Formation are limited. By conducting an integrated geophysical study, this report aims to increase the geological knowledge of Seri Iskandar by using geophysical approaches as geological information in the region is scarce.